Viabilitas probiotik Lacticaseibacillus rhamnosus SKG34 pada sari buah terung belanda (Solanum betaceum Cav.) terfermentasi selama penyimpanan pada suhu dingin - Nocianitri, Komang Ayu; Pratiwi, I Desak Putu Kartika; Wulandari, Kristina; Ramona, Yan; Sujaya, I Nengah (Agroindustrial Technology, University of Trunojoyo Madura, 2025)
Tamarillo (Solanum betaceum Cav.) is a tropical fruit that has the potential to be developed into functional food in the form of fruit juice containing probiotics. In order to develop the probiotic-containing product, the suitability of fruit juice to support the growth of probiotics and the viability of probiotics during the fermentation and storage processes are the prime concerns. Therefore, this study aims to determine the viability of the local probiotic Lacticaseibacillus rhamnosus SKG34 and the characteristics of fermented Tamarillo juice during storage at 4oC. Fermented tamarillo juice containing L. rhamnosus SKG34 is produced by fermenting Tamarillo juice with L. rhamnosus SKG34 and then stored at a temperature of ±4oC for 30 days. Population of L. rhamnosus SKG34, total sugar, total acid, pH, vitamin C, antioxidant capacity, and sensory characteristics were determined at 0, 5, 10, 15, 20, 25, and 30 days. The results showed that the probiotic L. rhamnosus SKG34 in fermented tamarillo juice was able to survive for 30 days with a population of 2.58 x 1010 CFU/ml from the initial population of 9.54 x 1010 CFU/ml. However, considering that chemical characteristics and other functional properties also influence the acceptability of fermented tamarillo juice, the optimal storage time is 20 days at 4oC. Under this condition, the fermented tamarillo juice containing 3.6 x 1010 CFU/ ml of L. rhamnosus SKG34; 11.23% sugars; total acid 0.98% acids; pH 3.44; 31.76 mg/100 ml vitamin C; and 4,725 GAEC/100 ml of antioxidant capacity, with favorable sensory levels.